The Effect of Health Education on the Attitudes and Practices of Food preservation and storage: Case study: Food and Drink Sellers in Tandalty City-White Nile State, 2021 – 2023 - Ali Saeed Ahmed Jad Kreem; Nour ELdeen ELtaher Fadlallah; Abdelrhman Ahmed Galaledin ALtijani (White Nile Journal for Studies and Research, 2023)
Introduction: Food is a substance that comes from animals or plants that are eaten to provide energy. Food contains the nutrition that people need to be healthy. People need protein, fat and carbohydrates. Vitamins and minerals.Study problem: Food and beverage sellers have bad behavior when dealing with food and beverages at the stage of storage and preparation, in addition to not providing ideal storage, lack of cleanliness of refrigerators and dry storage places, and lack of awareness of food storage pests and vector control methods. Study objectives: To assess the impact of health education on food storage trends and practices in the city of Tandalty - White Nile State 2021-2023. Results: The study showed a deficiency in the application of the health culture requirements of the study sample, as well as the presence of an open and full waste dump near the food preparation and sorting places that can attract insects, and when thawing frozen food does not leave enough time. Keywords: Tandalty City, food sellers, Food Storage, personal hygiene